Towards a digital transformation maturity model (DMTD) for credit unions [Hacia un modelo de madurez de transformación digital (MMTD) para las cooperativas de ahorro y crédito] (2020)
The formulation and implementation of a digital transformation strategy have become a key concern for many pre-digital organizations. Consequently, there is a fundamental need to support companies in the transition to the use of technologies and to guide them to improve their capabilities in a standardized, unbiased, and repeatable manner. The paper goal is presenting the first proposal for a Digital Transformation Maturity Model (DTMM) that meets the needs and challenges of the customer experience and is aligned with the characteristics of the credit unions. The methodology used is divided into six steps, starting with a systematic review of the literature on the subject, continuing with a semi-structured interview with experts in digital transformation, and then carrying out an information gathering with experts in the cooperative sector. All the above to validate the proposal of the dimensions and maturity levels associated with the MMTD. The results obtained are an MMTD structure for the cooperative sector with seven dimensions (1) Strategy, (2) Organization, (3) Customer, (4) Ecosystems, (5) Operations, (6) Technology, and (7) Innovation and their respective components. Also, five levels are proposed to evaluate the maturity of each dimension, Pioneers (Level 5), Optimized (Level 4), Integration (Level 3), Enablement (Level 2), Initiation (Level 1), and Not initiated (Level 0). © 2020, Associacao Iberica de Sistemas e Tecnologias de Informacao. All rights reserved.